2003
DOI: 10.1126/science.1086534
|View full text |Cite
|
Sign up to set email alerts
|

Separation of Metallic from Semiconducting Single-Walled Carbon Nanotubes

Abstract: We have developed a method to separate metallic from semiconducting single-walled carbon nanotubes from suspension using alternating current dielectrophoresis. Our method takes advantage of the difference of the relative dielectric constants of the two species with respect to the solvent, resulting in an opposite movement of metallic and semiconducting tubes along the electric field gradient. Metallic tubes are attracted toward a microelectrode array, leaving semiconducting tubes in the solvent. Proof of the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

18
1,074
2
10

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,463 publications
(1,124 citation statements)
references
References 19 publications
18
1,074
2
10
Order By: Relevance
“…[56] These electronic transition differences, however, make SWNT sample homogeneity a major issue. For example, even if a SWNT sample has been separated according to type (met-versus sem-) and d t , [64][65][66][67][68][69][70] different chirality and modality nanotubes will contribute significant heterogeneity as the nanotube diameter gets smaller than 1.5−2 nm. This is expected to play a significant role in the reproducibility of advanced nanotube devices as the community continues the refinement in coupling a variety of biological stimuli to SWNT electronic transitions.…”
Section: Carbon Nanotube Propertiesmentioning
confidence: 99%
“…[56] These electronic transition differences, however, make SWNT sample homogeneity a major issue. For example, even if a SWNT sample has been separated according to type (met-versus sem-) and d t , [64][65][66][67][68][69][70] different chirality and modality nanotubes will contribute significant heterogeneity as the nanotube diameter gets smaller than 1.5−2 nm. This is expected to play a significant role in the reproducibility of advanced nanotube devices as the community continues the refinement in coupling a variety of biological stimuli to SWNT electronic transitions.…”
Section: Carbon Nanotube Propertiesmentioning
confidence: 99%
“…Recent work has also demonstrated that it is possible to achieve limited separation of exfoliated SWNTs according to (n,m) structure, 58,121,136 left-or right-handed chirality, 95 length, 137,138 and electronic character (i.e., metallic or semiconducting). [139][140][141][142][143][144][145] SWNT surfactants are classified in terms of their ionic character (i.e., anionic, cationic, or nonionic). Ionic surfactants have a positively or negatively charged head group that interacts with the solvent and a nonpolar tail that associates with the nanotube sidewall; SWNT aggregation is hindered by charge repulsion between the polar head groups that extend into the solvent.…”
Section: Motivationmentioning
confidence: 99%
“…As the electronic property of an SWCNT strongly depends on its chirality, the lack of synthetic control in chirality has long been recognized as a fundamental impediment in the science and application of SWCNTs. Previous efforts to address this issue have resulted in significant progress in separation of synthetic mixtures, yielding predominantly single-chirality nanotube species [11][12][13][14][15] . However, separation processes are limited by their small scale, high cost and short length (o500 nm) of the resulting chirality-pure nanotubes.…”
mentioning
confidence: 99%
“…Our strategy is to combine nanotube separation with synthesis to achieve controlled growth of nanotubes with preselected chirality. Tremendous progress has been made in recent years in SWCNT separation [11][12][13][14][15]25,26 . In particular, DNA-based chromatographic separation allows purification of both semiconducting and metallic single-chirality SWCNTs through the use of different DNA sequences 12,26 .…”
mentioning
confidence: 99%